The Position of Online Ojek Based on the Perspective of Islamic Law - Muhammad Rafi’i; Fadia Fitriyanti; Moh. Lubsi Tuqo Romadhan; Susila; Nada Luqyana Mumtazah (International Journal of Social Science and Business, 2022)
In today's era, humans prioritize systems and business, but along with Islamic progress, Sharia-based economy and business are now starting to develop.  To meet daily needs, transportation is currently the urgent need for everyone. This is because transportation can support all activities in the community. This type of transportation too affects the rotation of activities that can be utilized in the economic sector, delivery of goods or services, and passenger transportation. This study aims to analyze the position of online ojek based on the perspective of Islamic law. Looking at the current development of the Islamic economy, many do not follow Islamic law in economic and business development. In this case, a compelling case for research is the development of the online transportation business. This study uses the normative juridical method. In normative research, to obtain data, you must use secondary data sources or library data and abuse laws and Hadith, or Al'qur'an as a writing reference.  So, from the discussion, we can see that online transportation service companies have succeeded in achieving Sharia business principles. This is all proven by economic progress and has created community welfare.